From TOLERANCE IS BUSINESS to TOLERANCE IS CLOTHING: Conceptual metaphors of religious tolerance in online Islamic mass media - Zakiyah, Millatuz; Saraswati, Destriana; Yulianto, Yulianto; Fadly, Ahmad Mufarih Hasan (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
So far, religious tolerance in the mass media has never been studied using metaphors in a cognitive linguistic approach. In fact, through conceptual metaphors, the framing of the mass media will emerge on the issue of religious tolerance. This qualitative descriptive research collects data on news and articles about religious tolerance in online Islamic mass media during the period 2018–2023. Data were analyzed using metaphor identification procedure, conceptual metaphor theory, and mixed metaphor. The results of the study show that there are 9 source domains, namely 1) TOLERANCE IS CLOTHES, (2) TOLERANCE IS SPACES/BUILDINGS, (3) TOLERANCE IS HUMANS, (4) TOLERANCE IS THE BODY, (5) TOLERANCE IS PLANTS, and (6) TOLERANCE IS ARE THINGS, (7) TOLERANCE IS A BUSINESS COMMODITY, (8) TOLERANCE IS WAR, and (9) TOLERANCE IS A VEHICLE. In general, the metaphor of tolerance in online Islamic mass media is classified into three tones, that is positive tones, negative tones, and neutral tones. Online Islamic mass media that have a positive tone are NU Online and Alif.id, mass media with a mixed tone (positive-neutral) is Suara Muhammadiyah and (positive-neutral-negative) is Hidayatullah.com, and mass media with a positive tone negative are Portal Islam, Suara Islam, VOA Islam, and Era Muslim.